Strategy of the Women's Empowerment and Child Protection Service and Population Control and Family Planning in Preventing Early Marriage in Murung Raya Regency, Central Kalimantan Province - Lynda Kristiane; Hyronimus Rowa; Faria Ruhana (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
This research is motivated by the still less than optimal strategy for preventing early marriage carried out by the Women's Empowerment and Child Protection Service, as well as Population and Family Planning Control, Murung Raya Regency. The purpose of the study was to analyze and determine the Strategy of the Women's Empowerment and Child Protection Service, as well as Population and Family Planning Control in Preventing Early Child Marriage in Murung Raya Regency, Central Kalimantan Province. Then using a descriptive qualitative method. The data sources used are primary data and secondary data. Data collection techniques through observation, interviews and documentation. Data analysis methods with data reduction, data presentation and drawing conclusions. The results of this study indicate that the Strategy of the Women's Empowerment and Child Protection Service, as well as Population and Family Planning Control in preventing early child marriage in Murung Raya Regency, Central Kalimantan Province. In the core strategy indicator, it is still not optimally carried out by the Women's Empowerment and Child Protection Service, as well as Population and Family Planning Control, Murung Raya Regency, this is evidenced by the results of the study that the strategy carried out has not been consistent in reducing the number of early marriages. In the consequence strategy indicator, Customer Strategy and control strategy have been implemented quite well. In the cultural strategy indicator, it has been implemented quite well, proven by the results of the study that the Women's Empowerment and Child Protection Service and Population and Family Planning Control of Murung Raya Regency strives to provide good services and can educate the community. The inhibiting factors in preventing early marriage in Murung Raya Regency, Central Kalimantan Province are limited human resources and lack of budget allocation. Efforts made by the Women's Empowerment and Child Protection Service and Population and Family Planning Control in preventing early marriage in Murung Raya Regency, namely, increasing human resources and increasing budget allocation